Acceptabilité sociale des mesures d’adaptation au changement climatique en zones côtières : une revue de dix enquêtes menées en France métropolitaine - Hélène Rey-Valette; Nicolas Rocle; Didier Vye; Lucile Mineo-Kleiner; Esméralda Longépée; Cécile Bazart; Nicole Lautrédou-Audouy (VertigO)
The article aims to compare and to analyze results from ten quantitative research surveys conducted in mainland France (from 2007 to 2017) dealing with citizen perceptions and points of view about coastal adaptation measures and policies to face sea level rise. Beyond social perceptions and representations on coastal phenomena and coastal risks, the article highlights the influence of institutional factors on adaptation policies’ acceptability depending on the type of population (primary and secondary residents, tourists…) : these factors are mainly the role of information, social perceptions of adaptation measures (protection, adjustment, coastal retreat…), trust and legitimacy about the institutions in charge of these policies, as well as feelings of (in)justice that are observed according to different propositions of funding in adaptation policies. Among the main convergent results, a majority of respondents express the feeling that they lack information about coastal risks and the way public authorities are engaged to tackle them. Moreover, a sequential approach for adaptation measures is expressed, where relocation is expected as a mid-term option after a period of protection and transition towards this type of operation. Regarding the conditions under which the different measures could be planned and conducted, a consensus seems to emerge in favor of a public leadership (especially by the State) where mechanisms of financial solidarity (at national or local scale) as well as procedures conducive to transparency and legitimacy of managing institutions are required.